Zakat-Based Islamic Philanthropy Supporting Maternal Health Equity Among Urban Poor Women in Banjarmasin - Falikhah, Nur; Putri; Fahriansyah (Program Studi Manajemen Dakwah Fakultas Dakwah dan Komunikasi UIN Sunan Ampel Surabaya, UIN Sunan Ampel Surabaya, 2026)
This study examines the role of zakat-based Islamic philanthropy in supporting maternal health equity among urban poor women in Banjarmasin within the framework of the Sustainable Development Goals (SDGs). Maternal health disparities indicate that vulnerable women continue to face barriers in accessing reproductive health services. Using a descriptive qualitative case study, this research was conducted at the Klinik Pratama Gratis Dhuafa Tersenyum managed by the Dhuafa Tersenyum Foundation. Data were collected through in-depth interviews, observations, and document analysis. The findings show that zakat, infaq, and sadaqah (ZIS) funds were utilised to provide free antenatal care, modern contraceptive services, and safe childbirth assistance. This zakat-based model complements government maternal health policies by reducing financial barriers, strengthening continuity of care, and supporting the achievement of SDG targets 3.1 and 3.7. The study highlights Islamic philanthropy as a socio-religious mechanism for equitable and sustainable maternal health policy implementation.